METHODICAL APPROACHES TO THE FORMATION AND EVALUATION OF ECONOMIC BEHAVIOR OF MODERN YOUTH - MERZLIKINA, YELYZAVETA; VASYLYSHYNA, LIUBOV (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article considers methodological approaches to the formation and evaluation of economic behavior of modern youth on the basis of statistical analysis of questionnaires. It is determined that the economic behavior of young people is formed, first of all, on the basis of the already existing model of economic behavior. The main conditions for the formation of economic behavior of young people are highlighted. It has been established that the main factor by which a person can influence his economic behavior is the establishment of the priority of values and needs. The order of formation of needs according to Maslow’s theory is considered. It is substantiated that for the formation of sustainable economic awareness of young people it is advisable to carry out various activities aimed at improving the level of economic behavior of young people. Particular attention should be paid to the implementation of youth projects. Local projects implemented during 2019-2020 are described, in particular «School of Success. Pokrovsk. 2019» and «Horizons of the Future 5.0_Pokrovsk». The strengths and weaknesses, opportunities and threats of each project are identified using the method of SWOT-analysis. Based on the results of the participation of youth representatives in the above-mentioned projects, it was hypothesized that no more than 70% of participants have a level of economic awareness at the level of secondary and higher. The level of economic behavior of the youth of the city of Pokrovsk was established by means of a survey. The reliability of the study was proved by using statistical Z-criterion, which confirms the hypothesis. The use of the proposed methodological approaches to the formation and evaluation of economic behavior of modern youth will create a basis for socio-economic development of an individual city, region and country as a whole.